Efektivitas Metode Tutor Sebaya dalam Mengatasi Kesulitan Belajar Fiqih Siswa: Studi di SMAN 1 Purwareja Klampok - Dewi Ngatikoh, Alessandra; Dwi Tantri2, Irma (Jurnal Pendidikan Agama Islam, 2025)
This research aims to examine the effectiveness of using the peer tutor method in overcoming students' fiqh learning difficulties. This research uses a quantitative approach with the type of research Quasi Experimental, control group design. The population in this study were XII grade students at SMA N 1 Purwareja Klampok which amounted to 356 students. Sampling in this study using Purposive Sampling technique, namely class XII-H and XII-J with a total of 34 students each. The data collection technique was done through a questionnaire. Data were analyzed descriptively and inferentially. The results of data testing through Mann Whitney show that the value of Sig. Asymp (2-tailed) = 0.001 (<0.05) which shows the difference in learning difficulties before and after treatment, with the questionnaire score after treatment lower than the score before treatment. This means that there is an effectiveness of using the peer tutor method in overcoming student learning difficulties at SMA N 1 Purwareja Klampok Banjarnegara.